DESAIN DAN UJI COBA VIDEO STOP MOTION SEBAGAI MEDIA PEMBELAJARAN PERKEMBANGAN TEORI MODEL ATOM - Nurul Arfah; Yuni Fatisa (Jurnal Pendidikan Kimia Universitas Riau, 2020)
This research was instigated by student difficulty in comprehending chemistry lesson that was theoretical, recitation and the lack of using instructional media. This research aimed at knowing the feasibility result of Stop Motion video as an instructional media especially on media lesson theoretical and recitation at State Vocational High School through validity test and practicality test. In this research Stop Motion video was designed by using Filmora application to support the learning on Development of Atomic Model Theory lesson. The final product was in the form of a valid tutorial video. It was a research and development (R&D) using model of Borg and Gall modification, and it was carried out at State Vocational High School 7 Pekanbaru. Interview and questionnaire were conducted for the techniques of collecting data. Stop Motion video as an instructional media developed was tested valid with 88.95% percentage (very valid) and practical with 82.75% (very practical). Based on these findings, it could be concluded that Stop Motion video as an instructional media on Development of Atomic Model Theory lesson have been valid and practical, and it got good student responses, so it could be tested in the next phase.